2020
DOI: 10.20944/preprints202012.0483.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-thinking the Foundation of Physics and its Relation to Quantum Gravity and Quantum Probabilities: Unification of Gravity and Quantum Mechanics

Abstract: In this paper we will show that standard physics to a large degree consists of derivatives of a deeper reality. This means standard physics is both overly complex and also incomplete. Modern physics has typically started from working with first understanding the surface of the world, that is typically the macroscopic world, and then forming theories about the atomic and subatomic world. And we did not have much of a choice, as the subatomic world is very hard to observe directly, if not impossible to observe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…This result should come as no surprise as already in 1960, Rindler [23] showed that the Minkowski space-time could be simplified from [2]. Further also in the moving system…”
Section: -Dimensional Space-time Geometrysupporting
confidence: 61%
See 4 more Smart Citations
“…This result should come as no surprise as already in 1960, Rindler [23] showed that the Minkowski space-time could be simplified from [2]. Further also in the moving system…”
Section: -Dimensional Space-time Geometrysupporting
confidence: 61%
“…In our theory, a collision between two light particles is the only pure mass, and the collision stands still. It is at absolute rest, see [2] [3], it takes up spatial dimensions as the light particles are similar to that suggested by Newton, namely indivisible and with spatial dimension, actually they have a diameter equal to the Planck length. That they have a diameter equal to the Planck length is not an assumption, this is what we find after calibrating our model to gravity observations.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations